Should Vitreo-retinal Diseases be Treated by Retina Specialists Only? - Hassan Raza Ch., Hussain Ahmad Khaqan, Abdul Hye (Pakistan Journal of Ophthalmology, 2016)
Purpose: To evaluate the views of ophthalmologists about referral and treatment of retinal disorders by vitreo-retinal (VR) surgeons Study Design: Cross Sectional Study. Place and duration of study: National Ophthalmic Conferences in Lahore, Karachi and Nathiya Gali (2014-2016) and Ophthalmological Society of Pakistan, Lahore Branch Monthly clinical Meetings (2014-2016). Material and Methods: A questionnaire based survey, involving 610 ophthalmologists was conducted through random sampling. The questionnaire was structured to evaluate the views about prescribing and treating with anti vascular endothelial growth factors (anti-VEGFs) and retinal lasers among random population of ophthalmologists. Survey was conducted during three national congresses and ophthalmological society monthly meetings and in different ophthalmology departments of the city. Results: Among 610 ophthalmologists from different parts of Pakistan enrolled for the survey, 200 were female and 410 male. Responses from all participants showed that 479 (78.5%) ophthalmologist were in favor that patients with vitreo-retinal disease should be referred to VR surgeons for treatment. Moreover, 472 (77.3%) ophthalmologists among 610 were in favor of intravitreal Anti-VEGF advise by vitreo-retinal surgeons. And 469(76.8%) ophthalmologist agreed that intravitreal anti-VEGF should be injected by vitreo- retinal surgeon. Only 279(45.73%) ophthalmologists among 610 thought that focal or PRP laser can be performed safely by general ophthalmologists. Conclusion: Ophthalmologists believe that retinal disorders should be referred to and treated by vitreo-retinal surgeons. Key words: Survey, Anti vascular endothelial growth factor, Intravitreal injections, Laser